Principal Instructional Leadership and the Reflective Culture of Elementary School Teachers in Batam - Priyanti Meinati Wulandari; Maya Novita Sari (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study analyzed the instructional leadership of school principals in strengthening teachers' reflective culture in public elementary schools in Sagulung District, Batam City. The study used a qualitative phenomenological approach. Data were collected through interviews, observations, and documentation involving principals and teachers selected purposively. The data were analyzed through condensation, data display, and conclusion drawing with verification. Credibility was strengthened through source and technique triangulation. The findings show that principals strengthened learning quality by formulating a data-based learning vision, conducting academic supervision, providing feedback, and building collaborative forums. However, teachers' reflection had not yet become a systematic school culture. The main constraints were uneven awareness of reflective practice, limited time due to teaching and administrative workloads, and the absence of structured instruments for documenting and following up reflection. The study concludes that instructional leadership becomes more effective when supervision is linked with collegial reflection, teacher learning communities, and measurable follow-up plans